ECOFISIOLOGIA E MORFOMETRIA COMO FERRAMENTA PARA O MANEJO SUSTENTÁVEL DE Eugenia pyriformis Cambess - Hellmann, Suélen Steinheuser (2017)
Eugenia pyriformis Cambess, commonly known as uvaia, is a native species of the southern region of Brazil and the state of São Paulo, occurs also in the Southeast, Goiás and Mato Grosso do Sul, which belongs to the Mirtaceae family, which includes a number of native species with economic potential due to its non-timber products (seeds, fruits, Oils) and loggers. It is known that Eugenia pyriformis Cambess has potential for reforestation of degraded areas due to its silvicultural characteristics, such as high regeneration rate, rapid growth and development, and also its early fruiting, however little is known about the domestication of the species. In this context, the objective of this work was to evaluate the ecophysiological characteristics and to demonstrate the morphometric relationships of the species Eugenia pyriformis Cambess with the purpose of providing subsidies for the development of its appropriate management. The work demonstrated the importance of the use of native species, relating physiological and morphometric characteristics of E. pyriformis Cambess, emphasizing the development of later work with the species with the objective of uncovering the growth and development of the species.